જો $x = 3 - \sqrt {5,} $ તો ${{\sqrt x } \over {\sqrt 2 + \sqrt {(3x - 2)} }} = $
$5$
$\sqrt 5 $
$1/5$
$1/\sqrt 5 $
${{{{2.3}^{n + 1}} + {{7.3}^{n - 1}}} \over {{3^{n + 2}} - 2{{(1/3)}^{l - n}}}} = $
${{3\sqrt 2 } \over {\sqrt 6 + \sqrt 3 }} - {{4\sqrt 3 } \over {\sqrt 6 + \sqrt 2 }} + {{\sqrt 6 } \over {\sqrt 3 + \sqrt 2 }} = $
સમીકરણ ${(x)^{x\sqrt x }} = {(x\sqrt x )^x}$ ના ઉકેલની સંખ્યા મેળવો.
જો ${a^{x - 1}} = bc,{b^{y - 1}} = ca,{c^{z - 1}} = ab,$ તો $\sum {(1/x) = } $
જો $x \ne 0 $ તો ${\left( {{{{x^l}} \over {{x^m}}}} \right)^{({l^2} + lm + {m^2})}}$${\left( {{{{x^m}} \over {{x^n}}}} \right)^{({m^2} + nm + {n^2})}}{\left( {{{{x^n}} \over {{x^l}}}} \right)^{({n^2} + nl + {l^2})}}=$